Observations of auroral plasma lines - Grydeland, Tom (Universitetet i Tromsø, 1998)
The thesis describes observations of strongly enhanced incoherent scatter plasma lines in the auroral ionosphere which were made with the EISCAT UHF radar in 1985. The linear theory of plasma instabilities is reviewed, and several possible explanations are discussed. The observations were found to be of insufficient resolution to unambiguously resolve which one would be the correct explanation. Finally, a new radar experiment design capable of making observations with higher resolution was realised and is presented in some detail.